POLITICAL AND ECONOMIC ASPECTS OF ANGLO-IRANIAN RELATIONS IN THE 19TH CENTURY (TAMADDUN NURI JURNALI, 2025)
This article examines the political and economic aspects of the relationship between Great Britain and Iran during the 19th century. Special attention is given to the influence of geopolitical interests, the “Great Game” between Britain and Russia, and the consequences of British policies for Iran’s internal development. The paper analyzes key diplomatic treaties, trade agreements, and the role of Britain in shaping Iran’s economic and political transformations.